Taurine and Astrocytes: A Homeostatic and Neuroprotective Relationship - Ramírez-Guerrero, Sofía; Guardo-Maya, Santiago; Medina-Rincón, Germán J.; Orrego-González, Eduardo E.; Cabezas-Pérez, Ricardo; González-Reyes, Rodrigo E. (Frontiers in Molecular Neuroscience, 2022)
Taurine is considered the most abundant free amino acid in the brain. Even though there are endogenous mechanisms for taurine production in neural cells, an exogenous supply of taurine is required to meet physiological needs. Taurine is required for optimal postnatal brain development; however, its brain concentration decreases with age. Synthesis of taurine in the central nervous system (CNS) occurs predominantly in astrocytes. A metabolic coupling between astrocytes and neurons has been reported, in which astrocytes provide neurons with hypotaurine as a substrate for taurine production. Taurine has antioxidative, osmoregulatory, and anti-inflammatory functions, among other cytoprotective properties. Astrocytes release taurine as a gliotransmitter, promoting both extracellular and intracellular effects in neurons. The extracellular effects include binding to neuronal GABAA and glycine receptors, with subsequent cellular hyperpolarization, and attenuation of N-methyl-D-aspartic acid (NMDA)-mediated glutamate excitotoxicity. Taurine intracellular effects are directed toward calcium homeostatic pathway, reducing calcium overload and thus preventing excitotoxicity, mitochondrial stress, and apoptosis. However, several physiological aspects of taurine remain unclear, such as the existence or not of a specific taurine receptor. Therefore, further research is needed not only in astrocytes and neurons, but also in other glial cells in order to fully comprehend taurine metabolism and function in the brain. Nonetheless, astrocyte’s role in taurine-induced neuroprotective functions should be considered as a promising therapeutic target of several neuroinflammatory, neurodegenerative and psychiatric diseases in the near future. This review provides an overview of the significant relationship between taurine and astrocytes, as well as its homeostatic and neuroprotective role in the nervous system.